Volatile aromatic substances analysis of different temperature stored ‘Docteur Jules Guyot’ pear (Pyrus communis L.) - Shi, Xiaomeng; Zhu, Xinxin; Xu, Xiaofei; Zhang, Xin; Jiang, Fudong; Li, Qingyu; Zhang, Aidi; Li, Jianzhao (Frontiers in Plant Science, 2025)
During the post-ripening process of ‘Docteur Jules Guyot’ pear, the aroma of the fruit gradually becomes richer with increasing maturity. In this study, the volatile substances in ‘Docteur Jules Guyot’ pear fruits stored at room temperature (RT), low temperature (LT), and low temperature to room temperature (LT-RT) were identified and analyzed using solid-phase microextraction (SPME) with gas chromatography–mass spectrometry (GC–MS) at different ripening stages. The results showed that the volatile substances were mainly alcohols, aldehydes, esters, acids, ketones, alkanes, and terpenes. Esters are the main substances of fruit aroma; with an increase in fruit maturity, the ester content increases gradually. Ethyl acetate, hexyl acetate, heptyl acetate, and amyl acetate were the main volatile components of the fruit. The aroma content under LT was lower than that under RT, and after transferring from LT-RT, the ripening of the fruit was accelerated, and the aroma content increased rapidly. Among the genes involved in the lox pathway, the expression of PcHPL1, PcADH1, PcGLIP1, PcGLIP-like, PcLOX2, PcLIP2, and PcFAD2 were the most contributing to the changes of esters in ‘Docteur Jules Guyot’ pear. These results are helpful to provide basic data for the study of volatile in ‘Docteur Jules Guyot’ pear fruit under LT and RT storage.